Ventricular arrhythmias associated with long-term endurance sports: what is the evidence? - Heidbuchel, H.; Prior, D. L.; La Gerche, A. (British Journal of Sports Medicine, 2012)
Athletic performance tests the limits of the human body and mind. Awe-inspiring achievements is what makes sports so fascinating. It is well appreciated however that top-level sports may sometimes overtax the body, and can lead to injuries, most notably of musculo-skeletal nature. This paper defends the thesis that the heart can also develop sports injuries at the ventricular level. We will elaborate on our hypothesis, originally put forward in 2003, that intense endurance activities put a particularly high strain on the right ventricle (RV), which over time, may lead to a proarrhythmic state resembling right (or less often) left ventricular cardiomyopathy. This can develop even in the absence of underlying demonstrable genetic abnormalities, probably just as a result of excessive RV wall stress during exercise. The syndrome of `exercise-induced arrhythmogenic RV cardiomyopathy` may easily be overlooked. Sports cardiologists, like orthopaedic specialists, should be prepared to realise that excessive sports activity can lead to cardiac sports injuries in some, which will help to council on safe participation in all.